Multimodality registration of two-dimensional echocardiography and cardiac CT for mitral valve diagnosis and surgical planning - Khalil A.; Faisal A.; Ng S.-C.; Liew Y.M.; Lai K.W. (SPIE, 2024)
A registration method to fuse two-dimensional (2-D) echocardiography images with cardiac computed tomography (CT) volume is presented. The method consists of two major procedures: temporal and spatial registrations. In temporal registration, the echocardiography frames at similar cardiac phases as the CT volume were interpolated based on electrocardiogram signal information, and the noise of the echocardiography image was reduced using the speckle reducing anisotropic diffusion technique. For spatial registration, an intensity-based normalized mutual information method was applied with a pattern search optimization algorithm to produce an interpolated cardiac CT image. The proposed registration framework does not require optical tracking information. Dice coefficient and Hausdorff distance for the left atrium assessments were 0.87±0.04 and 1.23±0.32mm, respectively; for left ventricle, they were 0.82±0.07 and 1.14±0.18mm, respectively. There was no significant difference in the mitral valve annulus diameter measurement between the manually and automatically registered CT images. The transformation parameters showed small deviations (≤1.14mm deviation in translation and <2deg for rotation) between manual and automatic registrations. The proposed method aids the physician in diagnosing mitral valve disease as well as provides surgical guidance during the treatment procedure.